Loss of function of Sco1 and its interaction with cytochrome c oxidase - Stiburek, Lukas; Vesela, Katerina; Hansikova, Hana; Hulkova, Helena; Zeman, Jiri (American journal of physiology. Cell physiology, 2009)
Sco1 and Sco2 are mitochondrial copper-binding proteins involved in the biogenesis of the Cu(A) site in the cytochrome c oxidase (CcO) subunit Cox2 and in the maintenance of cellular copper homeostasis. Human Surf1 is a CcO assembly factor with an important but poorly characterized role in CcO biogenesis. Here, we analyzed the impact on CcO assembly and tissue copper levels of a G132S mutation in the juxtamembrane region of SCO1 metallochaperone associated with early onset hypertrophic cardiomyopathy, encephalopathy, hypotonia, and hepatopathy, assessed the total copper content of various SURF1 and SCO2-deficient tissues, and investigated the possible physical association between CcO and Sco1. The steady-state level of mutant Sco1 was severely decreased in the muscle mitochondria of the SCO1 patient, indicating compromised stability and thus loss of function of the protein. Unlike the wild-type variant, residual mutant Sco1 appeared to migrate exclusively in the monomeric form on blue native gels. Both the activity and content of CcO were reduced in the patient's muscle to approximately 10-20% of control values. SCO1-deficient mitochondria showed accumulation of two Cox2 subcomplexes, suggesting that Sco1 is very likely responsible for a different posttranslational aspect of Cox2 maturation than Sco2. Intriguingly, the various SURF1-deficient samples analyzed showed a tissue-specific copper deficiency similar to that of SCO-deficient samples, suggesting a role for Surf1 in copper homeostasis regulation. Finally, both blue native immunoblot analysis and coimmunoprecipitation revealed that a fraction of Sco1 physically associates with the CcO complex in human muscle mitochondria, suggesting a possible direct relationship between CcO and the regulation of cellular copper homeostasis.
Keywords: Mitochondria; játra; Membrane Proteins; Fetal Growth Retardation; Infant; Humans; kojenec; molekulární chaperony; Copper; kardiomyocyty; ledviny; Female; kůže; Kidney; lidé; mitochondrie; Mitochondrial Proteins; Myocytes, Cardiac; mitochondriální proteiny; Molecular Chaperones; transportní proteiny; měď; buněčné linie; Carrier Proteins; ženské pohlaví; Cell Line; respirační komplex IV; homeostáza; Liver; růstová retardace plodu; Homeostasis; membránové proteiny; fibroblasty; Electron Transport Complex IV; Skin; Fibroblasts